FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI INDUSTRI GENTENG DI KABUPATEN TABANAN TAHUN 2021 - Ni Komang Mela Tri Utari; Ni Luh Laksmi Rahmantari (Yayasan Nusantara Hasana Berdikari, 2023)
Tabanan Regency is one of the regencies/cities in Bali Province which has great potential in the small industrial sector which is absorbed into several sectors of Micro, Small and Medium Enterprises (MSMEs) spread to several areas in Tabanan Regency. The development of the amount of production produced by the tile industry in Kediri District, Tabanan Regency in a five-year period has fluctuated Based on these problems, it is necessary to do research on what factors affect production in the tile industry in Kediri District, Tabanan Regency in 2021, with the aim of knowing the effect of labor and capital on production in the tile industry in Kediri District, Tabanan Regency. 2021, either partially or simultaneously. Sampling in this study, carried out with a saturated sample technique, as many as 65 business units of the tile industry in Kediri District, Tabanan Regency. The data analysis technique used multiple linear regression analysis. The results show that labor and capital partially have a positive and significant effect on production in the roof tile industry in Kediri District, Tabanan Regency in 2021. Furthermore, labor, length of business and capital simultaneously have a significant effect on production in the roof tile industry in the District. Kediri Tabanan Regency in 2021, with a clear power of 91,5 percent.